2013
DOI: 10.1007/978-3-319-02526-1_2
|View full text |Cite
|
Sign up to set email alerts
|

Citation Practices of Expert French Writers of English: Issues of Attribution and Stance

Abstract: In research articles (RAs), reporting the results and claims of other authors is a crucial skill as it both demonstrates the writers' familiarity with the literature of the field and allows them to position their own findings and conclusions within the existing body of research, thus creating space to promote their work. Using citations effectively, however, demands considerable linguistic and rhetorical expertise. While several studies have shown that citation causes problems for novice researchers, the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…İlk araştırma sorusu ile bağlantılı bulgular DY'ların DsizY'lardan yaklaşık iki kat daha fazla atıf kullandıklarını ortaya koymuştur. Bu bulgu, Anglo-Amerikan araştırmacılarının ana dili İngilizce olmayan yazarlara göre daha fazla atıf kullandıklarını ortaya koyan önceki çalışmaların bulguları ile uyuşmaktadır (Mur Duenas, 2009;Rowley-Jolivet ve Carter-Thomas, 2014;Taylor ve Chen, 1991). Başka bir deyişle, bulgular, deneyimsiz yazarların sınırlı sayıda atıf türünü kullandıklarını ortaya koyan önceki araştırmaların bulgularını desteklemektedir (Thompson ve Tribble, 2001).…”
Section: Discussionunclassified
“…İlk araştırma sorusu ile bağlantılı bulgular DY'ların DsizY'lardan yaklaşık iki kat daha fazla atıf kullandıklarını ortaya koymuştur. Bu bulgu, Anglo-Amerikan araştırmacılarının ana dili İngilizce olmayan yazarlara göre daha fazla atıf kullandıklarını ortaya koyan önceki çalışmaların bulguları ile uyuşmaktadır (Mur Duenas, 2009;Rowley-Jolivet ve Carter-Thomas, 2014;Taylor ve Chen, 1991). Başka bir deyişle, bulgular, deneyimsiz yazarların sınırlı sayıda atıf türünü kullandıklarını ortaya koyan önceki araştırmaların bulgularını desteklemektedir (Thompson ve Tribble, 2001).…”
Section: Discussionunclassified
“…The use of reporting verbs is also influenced by L1. The possible effect of L1 on the use of reporting structures in English was explored by Rowley-Jolivet and Carter-Thomas (2014), who showed that using reporting verbs represented a problem for expert French writers of English. Consequently, because of the limited use of certain reporting and conversational verbs, Parkinson (2013) recommends more explorations of students' use of reporting verbs.…”
Section: Introductionmentioning
confidence: 99%
“…The citation is the most distinctive feature of language use in academic disciplines as citing and referring to other authors' studies are basic for the persuasiveness and the acceptance of academic arguments (Hewings, Lillis, & Vladimirou, 2010;Mansourizadeh & Ahmad, 2011;Maroko, 2013;Monreal & Salom, 2011;Nguyen & Pramoolsook, 2015;Rowley-Jolivet & Carter-Thomas, 2014;Samraj, 2013;Shooshtari & Jalilifar, 2010;Swales, 2014;Thompson & Tribble, 2001). Hence, citations have attracted much research attention (Hu & Wang, 2014).…”
Section: Perspectives Of Efl Doctoral Students On Challenges Of Citatmentioning
confidence: 99%
“…The process of citing information involves several significant issues, such as what to cite, who to cite, how to cite, and when not to cite (Polio & Shi, 2012). Hence, citing information from articles, theses or dissertations is challenging, particularly for researchers who write in English as a second or foreign language (Law et al, 2013;Nguyen & Pramoolsook, 2016;Rabab'ah & Al-Marshadi, 2013;Rowley-Jolivet & Carter-Thomas, 2014). Citation practices may vary across disciplines (Hyland, 1999;Jomaa & Bidin, 2016;Swales, 2014) and cultures (Rowley-Jolivet & Carter-Thomas, 2014).…”
Section: Perspectives Of Efl Doctoral Students On Challenges Of Citatmentioning
confidence: 99%